Asylum, immigration and statehood - a philosophical perspective - Matthias Oschinski (Transformation, Integration and Globalization Economic Research (TIGER), 2005)
According to UNHCR, the number of refugees and people of the UNHCR's concern exceeds 20 million. This number, though very large, is still understated as it accounts only for those individuals who actually fulfil UNHCR's definition of a refugee. The true number of people in adversity, in need of another state's help, in search for a better life, is much higher than this officially announced figure. Next to legal and political implications, this poses a moral problem to the rest of the world population - how are we to treat refugees, asylum seekers and migrants in general; what possible duties or obligations do foreign states have towards this group of outsiders? This paper undertakes to explore the moral claims outsiders might have towards a foreign nation-state. Accordingly, the following questions will be addressed: First, is a state obliged to assist and help refugees and on what grounds can these obligations be based? Second, do migrants possess any rights towards a given nation-state and, if so, from what reasoning might those rights be derived? By analyzing these questions applying competing moral theories, the paper arrives at the conclusion that there cause for a thorough rethinking of the concepts of statehood and citizenship.
Keywords: 330; Flüchtlinge; Philosophie; Migranten; Ethnische Beziehungen